Balancing and Rebalancing in the Creation and Evolution of Organizational Control - Cardinal, Laura B.; Sitkin, Sim B.; Long, Chris P. (Organization Science, 2004)
This research examines data collected as part of a 10-year case study of the creation and evolution of organizational control during organizational founding. Past research has taken a cross-sectional approach to examining control use in mature, stable organizations. In contrast, this study examines organizational controls during the founding period and takes a longitudinal perspective on organizational control. By examining how organizational controls are created and evolve through specific phases of the founding period, the research also provides new data and insights about what drives shifts in the use of various types of control. Specifically, this research sheds light on the role of imbalance among formal and informal controls as the key driver of shifts in control configurations, and provides a step toward making organizational control theory more dynamic.